Prayer Guide Gyroscope Bracelet for The Deaf Using MPU6050 Sensor - Heriyadi, Heriyadi; Fajrin, Hanifah Rahmi; Kartika, Wisnu (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
The majority of Indonesia's population is Muslim, including more than 13,000 people with hearing impairments. In carrying out congregational prayers, the Deaf find it difficult to follow the instructions of the Imam's movement. The presence of hearing aids cannot be used by all persons with hearing impairments, and hearing aids often cause a buzzing sound, thus disturbing concentration. Therefore, in this study, a gyroscope bracelet will be made to assist people with hearing impairments in following the instructions of the Imam's movement when carrying out congregational prayers. The bracelet worn by the Imam will send a code in the form of a change in angle to the bracelet used by the Deaf congregation. The Z angle is a vertical angle in the gyroscope where the Z angle has an angular velocity of 360 degrees per second. The control system uses Arduino nano FT232RL FTDI FT232. The communication module uses HC-12 SI4463, with a wireless frequency of 433.4 - 473.0 MHz. The sensor for detecting changes in motion is the MPU6050 gyroscope sensor, the vibration indicator uses a micro vibrator motor. The bracelet used by the deaf will read the code from the Imam's device, with a notification in the form of a different vibration on every change in prayer movement. After experimenting with 30 people, the percentage of success was 84% ​​for all prayer positions. Thus, the gyroscope bracelet tool for prayer guides for the Deaf can help the Deaf community in carrying out congregational prayers.